K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 12 2018

\(a,4x-2=0\)

\(4x=2\)

\(x=\frac{1}{2}\)

\(b,x^2+5x-14=0\)

\(x^2-2x+7x-14=0\)

\(x\left(x-2\right)+7\left(x-2\right)=0\)

\(\left(x-2\right)\left(x+7\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x-2=0\\x+7=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=2\\x=-7\end{cases}}}\)

=.= hk tốt!!

23 tháng 12 2018

\(a,20xy-10x=10x\left(2y-1\right)\)

\(b,6x-6y+x^2-y^2\)

\(=6\left(x-y\right)+\left(x-y\right)\left(x+y\right)\)

\(=\left(x-y\right)\left(6+x+y\right)\)

23 tháng 12 2018

1)

a) \(20xy-10x=10x\left(2y-1\right)\)

b)\(6x-6y+x^2-y^2\)

\(=6\left(x-y\right)+\left(x-y\right)\left(x+y\right)\)

\(=\left(x-y\right)\left(6+x+y\right)\)

23 tháng 12 2018

ai trả lời đúng mk cho

23 tháng 12 2018

\(B=\left(\frac{1}{2-x}+\frac{3x}{x^2-4}-\frac{2}{2+x}\right):\left(\frac{x+4}{4-x^2}+4\right)\)\(=\left(\frac{1}{2-x}+\frac{3x}{x^2-4}-\frac{2}{2+x}\right):\left(\frac{-x-4}{x^2-4}+4\right)\)

\(=\left(\frac{-1}{x-2}+\frac{3x}{\left(x-2\right)\left(x+2\right)}+\frac{-2}{x+2}\right):\left(\frac{-x-4+4x^2-16}{\left(x-2\right)\left(x+2\right)}\right)\)

\(=\left(\frac{\left(-1\right)\left(x+2\right)}{\left(x-2\right)\left(x+2\right)}+\frac{3x}{\left(x-2\right)\left(x+2\right)}+\frac{\left(-2\right)\left(x-2\right)}{\left(x-2\right)\left(x+2\right)}\right)\)\(:\left(\frac{4x^2-x-20}{\left(x-2\right)\left(x+2\right)}\right)\)

\(=\left(\frac{-x-2+3x-2x+4}{\left(x-2\right)\left(x+2\right)}\right).\frac{\left(x-2\right)\left(x+2\right)}{4x^2-x-20}\)

\(=\frac{2}{\left(x-2\right)\left(x+2\right)}.\frac{\left(x-2\right)\left(x+2\right)}{4x^2-x-20}\)

\(=\frac{2}{4x^2-x-20}\)

22 tháng 12 2018

\(B=\frac{2x^2-2}{x^3+x^2-x-1}=\frac{2\left(x-1\right)\left(x+1\right)}{x^2\left(x+1\right)-\left(x+1\right)}=\frac{2\left(x-1\right)\left(x+1\right)}{\left(x-1\right)\left(x+1\right)^2}\)

\(ĐKXĐ:x\ne\pm1\)(1)

\(\)\(B=\frac{2}{x+1}\)

Để B thuộc Z => \(2⋮x+1\left(x\in Z\right)\)

\(\Rightarrow\left(x+1\right)\inƯ\left(2\right)=\left(1;-1;2;-2\right)\)

\(\Rightarrow x\in\left(0;-2;1;-3\right)\)(2)

từ (1) và (2)

\(\Rightarrow x\in\left(0;-2;-3\right)\)